FENOMENA KOMUNIKASI VIDGRAM PADA KOMUNITAS @PKUVIDGRAM - Annisa Fitriani; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The phenomenon of vidgram was present at a time when a group of young Indonesians who were literate with technology, using Instagram as a new means of entertainment for the Indonesian people. This study aims to determine the motives, meaning and communication experience of community members @pkuvidgram in uploading vidgram in Instagram.A method of this research is qualitative methods with the presentation of data analysis descriptively and using phenomenology theory Alfred Schutz. The subject of research is determined by purposive technique consisting of 6 informants from community member @ pkuvidgram. Data collection techniques include observation, interviews and documentation. Data analysis techniques using interactive data models Miles and Huberman. While the technique of examining the validity of data include triangulation and reference adequacy.The results of this study indicate that the past motives of informants in uploading vidgram is a hobby watching comedy and interest in multimedia. The future motive of the informant is to entertain others, want to convey messages, want to add followers, want to get lots of friends and want to get endorse. The meaning of vidgram upload activity for informants is vidgram as a medium to entertain, vidgram as a medium of self expression, and vidgram as additional income. The pleasant communication experience experienced by the informant is in the form of winning the race, gaining popularity, earning many endorse, following community event, and reposted back by @indovidgram account. While the unpleasant experience of being considered weird by friends, getting negative comments, expelled by security guards, ideas taken by others, and error devices.Keywords: communication phenomena, vidgram, @pkuvidgram community